Iranian vernacular ice-house: Notable example of a traditional architecture in proportion to its climate conditions - Izadpanahi, Parisa; Amirkhani, Arian; Seddigh, Morteza; Eskandari, Manije; Yazdanpanah, Parisa (Human Resource Management Academic Research Society, 2010)
Iranian architecture is shaped in related to its Hot-Dry climate and has provided interesting answers to the Iranian's needs. In this climate, most of the buildings are constructed by mud or sun-dried bricks. There are so many facilities that Iranian architecture has provided for better living such as: Wind-Catcher (which exhausts warm air from buildings during the day), Cisterns (which have a cylindrical store place in the depth of the earth for storing the cold fresh water during the hot seasons), Ice-Houses with walls behind which water in shallow channels friezes at nights, etc. The great heritage of Iranian architecture and traditions are still not known until now. The constructing traditions of vernacular architecture in Iran, reveals the mystery of using natural energy sources that reduce the need to fossil fuel. Among different Iranian cultural heritage, Ice-Houses are selected as the main subject of this article.